2002
DOI: 10.3136/fstr.8.252
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration Differences in Cooked Potatoes from Three Japanese Cultivars: Comparison of Starch Distribution within One Tuber and Tissue Structure.

Abstract: Differences in the degree of disintegration after cooking were studied in three potato cultivars: Kita-akari, May Queen, and Hokkaikogane. Although the degree of disintegration increased with increase in the starch content in these cultivars, there were even differences in cultivars with identical starch content. For example, at 16%, the disintegration in Kita-akari, according to the standard grades for breeding, was "moderate-complete;" that of May Queen, "moderate;" and that of Hokkaikogane, "none." Microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…One hundred percent of the Kita-akari value corresponds to 336.9 mg/100 g FW. (Matsuura-Endo et al , 2002). These factors could closely relate to the disintegration degree of each cultivar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred percent of the Kita-akari value corresponds to 336.9 mg/100 g FW. (Matsuura-Endo et al , 2002). These factors could closely relate to the disintegration degree of each cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that differences in the starch distribution within one tuber and tissue structure may cause differences in the degree of disintegration in cultivars with identical starch content (Matsuura-Endo et al , 2002). To understand the effects of starch on disintegration, the starches of three cultivars were isolated and their properties were compared.…”
Section: Discussionmentioning
confidence: 99%
“…The sloughing degree is usually assessed visually (Hegney and McPharlin 2000, Matsuura-Endo et al 2002a, Searle et al 2005. Different modifications of sloughing tests associated with measurements of the degree of cell separation were used (Freeman et al 1992, Van Marle et al 1994, Matsuura-Endo et al 2002b.…”
mentioning
confidence: 99%
“…These relationships could indicate that the harder cortex was composed of smaller cells and forces of cell wall binding, and if the cortex was difficult to break, sweetness declines accompanied by an increase in potato taste. In boiled potato tubers, smaller cortex cells have larger binding areas for each unit cell volume than bigger cells, and the cells are hard to separate in cortex that constructed with small cell (Matsuura-Endo et al 2002), which could be explained by the chemicals related strongly to sweetness remaining inside cells, and chemicals related to potato taste being in apoplastic spaces. But the relationship between difficulty of collapsed cells and chemical flavor is still unclear because of no evidence in this study.…”
Section: Discussionmentioning
confidence: 98%